Phenacoccus solenopsis Tinsley (Sternorrhyncha: Coccoidea: Pseudococcidae), an invasive mealybug damaging cotton in Pakistan and India, with a discussion on seasonal morphological variation - Hodgson, Chris; Abbas, Ghulam; Arif, Muhammad Jalal; Saeed, Shafqat; Karar, Haider (Zootaxa, 2008)
Since at least 2005, a possibly introduced mealybug of the genus Phenacoccus has been causing serious damage to cotton (Gossypium hirsutum) over much of the Sindh and Punjab districts of Pakistan and in north-western India. Some short papers have been published locally giving details on the structure and biology of this species and suggesting the name Phenacoccus gossypiphilous Abbas, Arif & Saeed (2005) but without designating type specimens or depositories. This name is here considered a nomen nudum. A detailed morphological study has been unable to separate this species from many specimens of Phenacoccus from the Neotropics that are believed to be Phenacoccus solenopsis Tinsley. The material from the Indian subcontinent shows considerable morphological variation in the frequency of multilocular disc pores and oral collar tubular ducts on the ventral submargin of the abdomen; this appeared to be related to conditions under which this species was reared, with those cultured in a screen-house during the non-cotton-growing season being indistinguishable from P. solenopsis from the Neotropics . This paper re-describes the adult female of P. solenopsis Tinsley based on the type specimens from New Mexico, and designates a lectotype. The type material was compared with specimens considered to be P. solenopsis from elsewhere in the New World, and from West Africa and several areas in Asia, particularly Pakistan and India. Based of our present understanding of the morphology of adult female P. solenopsis, it is concluded that the species is rather variable, that this variability may be environmentally induced, and that the species currently causing widespread damage to cotton on the Indian subcontinent is referable to P. solenopsis. Adult male P. solenopsis from North America, Pakistan and India were also studied and again no significant differences were found. Descriptions are provided of the adult male and all the immature stages of P. solenopsis, based on material from India and Pakistan. Keys are provided to (a) separate P. solenopsis from similar species of Phenacoccus currently known from Asia and (b) to identify all instars. The morphological differences between P. solenopsis, P. solani Ferris and P. defectus Ferris are reviewed and, based on the morphological variation found in the Asian material, it is considered that there is some support for the suggestion that these three species might be environmentally induced variants of a single species. A few details are given of the biology of P. solenopsis on cotton in Pakistan.